IMPLEMENTATION OF CENTRAL BANK DIGITAL CURRENCY (CBDC) IN STRENGTHENING THE PAYMENT SYSTEM - Fuddin, Muhammad; Oktavia, Aisyah; Maulidiyah, Ivada; Raharjo, Saddam; Buana, Cahaya (Accounting Department, Politeknik Negeri Bandung, 2024)
The purpose of this study is to determine the characteristics of CBDCs and to determine central banks' views on CBDCs that can be utilized and achieve their goals in the digital acceleration of the financial services sector. This study provides an overview of the development of digital currencies created by central banks. This study uses the paper review method using VOS viewer software. Researchers can analyze several previous studies' shortcomings, so they can improve and formulate to be more organized and systematic. The results of this study state that the Central bank Digital Currency (CBDC) has several characteristics, namely 1) A practical means of exchange without fees, where CBDCs are account-based whose accounts can be deposited directly at the Central Bank. 2) A safe store of value, interest rates in a CBDC will provide a rate of return commensurate with a risk-free asset. 3) Gradual currency obsolescence, whereby the general public can use CBDCs with low transfer fees. 4) Actual price stability, the value of the CBDC has remained stable over time concerning the CPI